2012
DOI: 10.1007/s10495-012-0737-y
|View full text |Cite
|
Sign up to set email alerts
|

Label-free monitoring of apoptosis by surface plasmon resonance detection of morphological changes

Abstract: Apoptosis can be routinely characterized using biomolecular markers such as in the TUNEL and the annexin V assays or by using fluorescent caspase substrates. Apoptosis can also be semi-quantitatively characterized using microscopy, which targets morphological features such as cell rounding, nuclear condensation and fragmentation as well as cell membrane blebbing. This label-free approach provides a limited resolution for the evolution of these events in time and relies heavily on subjective identification of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…The custom-built SPR apparatus has been described in details in previous publications 44,45 and was applied by our group for the monitoring of apoptosis in a realtime manner 46 . SPR measurements were done by measuring the reflectance at a fixed angle in the quasi-linear section of the angular scan (i.e.…”
Section: Spr Substrates and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The custom-built SPR apparatus has been described in details in previous publications 44,45 and was applied by our group for the monitoring of apoptosis in a realtime manner 46 . SPR measurements were done by measuring the reflectance at a fixed angle in the quasi-linear section of the angular scan (i.e.…”
Section: Spr Substrates and Analysismentioning
confidence: 99%
“…First, surface plasmon resonance (SPR) was used as a label-free assay to follow apoptosis in real-time 46 . Figure 2 shows that A7r5 cells display a robust reflectance decline starting 4 hours after stimulation with CML-HSA, reaching 75.6 ± 2.8% of the maximum possible decrease after 20 hours.…”
Section: Spr Response Of Vsmc To Rage Activationmentioning
confidence: 99%
“…Gold substrates were prepared and surface plasmon resonance (SPR) experiments were conducted as previously described (Cuerrier et al, 2008;Maltais et al, 2012). The HEK FlagMOP cells were grown to confluence on a gold substrate surface precoated with a solution of 5 mg/ml fibronectin (Sigma-Aldrich) and 200 mg/ml gelatin (BD, Franklin Lakes, NJ).…”
Section: Surface Plasmon Resonance Measurementsmentioning
confidence: 99%
“…For example, Stallaert et al (2012) used an impedance-based system to assess functional selectivity at the b 2 adrenergic receptor, whereas Morse et al (2011Morse et al ( , 2013 used an optical-based system to assess opioid receptor signaling. We previously showed that SPR represents a valuable label-free technique to monitor GPCR signaling and apoptosis (Cuerrier et al, 2008;Chabot et al, 2009;Maltais et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Because of the advantage of sensitive, real-time, and label-free, SPR cell detection has drawn much attention. [20][21][22] It has been proved that cellular morphologic change, 23,24 cell-substrate interactions, 25,26 and even the ligand-induced intracellular signaling events 27,28 can be monitored by SPR in real time. Recently, SPR has been combined with other techniques, such as electrochemical measurement, nanoparticles, and microscope imaging, for multi-parametric cell profiling.…”
Section: Introductionmentioning
confidence: 99%